2016
DOI: 10.1073/pnas.1522112113
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of substrate specificity of phosphatidylinositol phosphate kinases

Abstract: The phosphatidylinositol phosphate kinase (PIPK) family of enzymes is primarily responsible for converting singly phosphorylated phosphatidylinositol derivatives to phosphatidylinositol bisphosphates. As such, these kinases are central to many signaling and membrane trafficking processes in the eukaryotic cell. The three types of phosphatidylinositol phosphate kinases are homologous in sequence but differ in catalytic activities and biological functions. Type I and type II kinases generate phosphatidylinositol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(64 citation statements)
references
References 44 publications
(50 reference statements)
3
61
0
Order By: Relevance
“…This class is mainly responsible for the generation of a large fraction of the PtdIns-3-phosphate, a central phospholipid for membrane trafficking processes [123]. PtdIns kinases appear to strongly prefer ATP as the phosphate donor [119]. The structure forms two domains of approximately equal size (shown in teal and raspberry; PDB ID: 1WUU [36]).…”
Section: Overview Of the Family And Specificitymentioning
confidence: 99%
“…This class is mainly responsible for the generation of a large fraction of the PtdIns-3-phosphate, a central phospholipid for membrane trafficking processes [123]. PtdIns kinases appear to strongly prefer ATP as the phosphate donor [119]. The structure forms two domains of approximately equal size (shown in teal and raspberry; PDB ID: 1WUU [36]).…”
Section: Overview Of the Family And Specificitymentioning
confidence: 99%
“…The cognate ATP kinase PI4P5Kα also interacts with ATP in the same binding mode ( Fig. 2A, middle) (Muftuoglu et al, 2016).…”
Section: The Atp Recognition Mode Is Shared Among Protein and Lipid Kmentioning
confidence: 88%
“…Our assay can be used to identify ATP-non-competitive compounds, like it was shown for the substratecompetitive compound 13. Muftuoglu et al [24] in their study about the mechanism of substrate specificity of PIPKs found out that the substrate binding site is in closed vicinity to the ATP binding site. This finding might be a reason for the uncorrelated docking results with the actual binding mode.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to natural PI(4)P and PIP 2 , PI(4)P fluorescein and PIP 2 fluorescein have truncated fatty acid chains and an additional fluorescein moiety conjugated to the end of one chain. It was shown for the zebrafish enzyme that only the polar inositol head group of the lipid is recognized by the active site of the enzyme [24]. Due to the fact that a reliable separation method was available, we decided to test whether the artificial phosphoinositide PI(4)P fluorescein is accepted as substrate by hPIP5K1a, leading to the corresponding fluorescent product (Fig.…”
Section: Activity Assaymentioning
confidence: 99%